Changes in growth, morphology, and levels of digestive enzymes and growth-related hormones in early ontogeny of black scraper, Thamnaconus modestus - Liu, Liming; Zeng, Jun; Zhang, Zhe; Wang, Jiulong; Mei, Weiping; Wang, Chengwu; Liu, Zhenpeng; Xu, Wengang (Frontiers in Marine Science, 2024)
Introduction The black scraper, Thamnaconus modestus, is a highly valued marine fish species, but its output has gradually decreased in recent years, which may be due to its low survival rate during early ontogenesis. Methods Therefore, in this study, we assessed the changes in growth, morphology, digestive enzymes, and hormone levels in T. modestus from 0–60 days post-hatching (dph) and revealed growth turning points by morphological measurement and determination of digestive enzyme activities and hormone levels. We found that ontogenesis could be divided into the larval (0–20 dph) and juvenile (20–60 dph) stages. Acid and alkaline protease activity significantly increased and decreased, respectively, from 12–25 dph, likely due to the development of stomach and gastric glands. Acid phosphatase levels significantly increased at 0 and 4 dph, which may be related to the regulation of metabolism and immune protection. A sharp increase in alkaline phosphatase levels at 20 and 25 dph was observed and was likely due to the development of the brush border membrane of enterocytes. The amylase level was significantly higher at 25, 30, and 35 dph, possibly due to better digestion and absorption during the transition from consuming Artemia to compound feed. In newly hatched larvae, the level of thyroid hormones triiodothyronine (T3) and thyroxine (T4) gradually increased and peaked at 35 dph, highlighting the importance of these hormones during the development of T. modestus. Growth hormone (GH) levels first increased from 0–8 dph, with a plateau at 8–20 dph, and then increased at 25–30–35 dph. For insulin-like growth factor 1 (IGF-1), a significant increase with a subsequent plateau was observed between 8 and 20 dph, followed by a substantial decrease between 30 and 35 dph. These results suggest that the regulating functions of GH and IGF-1 are synchronised. Digestive enzyme activity and hormone levels of abnormal fry at 30 dph were lower than those of normal fish, highlighting the importance of specific hormones, especially T4 and IGF-1, in the development of T. modestus.